Genetic analysis of Bacillus stearothermophilus by protoplast fusion. - Chen, Z F (1986)
Efficient and reliable protoplasting, regeneration, and fusion techniques were established for the prototrophic strain Bacillus stearothermophilus NUB36. Auxotrophic mutants were isolated, and protoplast fusion was used to construct isogenic mutant strains and for chromosomal mapping. Markers were mapped using two-, three-, and four-factor crosses. The order of the markers was hom-1-thr-1-his-1-(gly-1 or gly-2)-pur-1-pur-2. These markers may be analogous to hom, thrA, hisA, glyC, and purA markers on the Bacillus subtilis chromosome. No analogous pur-1 marker has been reported in B. subtilis. The relative order of three of the markers (hom-1-thr-1-gly-1) was independently confirmed by transduction.